Biodiesel production from Nannochloropsis gaditana lipids through transesterification catalyzed by Rhizopus oryzae lipase. (March 2016) - Navarro López, Elvira; Robles Medina, Alfonso; González Moreno, Pedro Antonio; Esteban Cerdán, Luis; Martín Valverde, Lorena; Molina Grima, Emilio
Graphical abstract: Highlights: Saponifiable lipids (SLs) were extracted from wet biomass using ethanol and hexane. Intracellular R. oryzae lipase catalyzed the methanolysis of microalgal SLs. Biodiesel yield and lipase reuse were higher using SLs poorer in polar lipid. Biodiesel yield and lipase reutilization were higher in tert-butanol than in hexane. 83% of microalgal SLs were transformed to biodiesel in the optimized conditions. Abstract: Biodiesel (fatty acid methyl esters, FAMEs) was produced from saponifiable lipids (SLs) extracted from wet Nannochloropsis gaditana biomass using methanolysis catalyzed by Rhizopus oryzae intracellular lipase. SLs were firstly extracted with ethanol to obtain 31 wt% pure SLs. But this low SL purity also gave a low biodiesel conversion (58%). This conversion increased up to 80% using SLs purified by crystallization in acetone (95 wt% purity). Polar lipids play an important role in decreasing the reaction velocity – using SLs extracted with hexane, which have lower polar lipid content (37.4% versus 49.0% using ethanol), we obtained higher reaction velocities and less FAME conversion decrease when the same lipase batch was reused. 83% of SLs were transformed to biodiesel using a 70 wt% lipase/SL ratio, 11:1 methanol/SL molar ratio, 10 mL t-butanol/g SLs after 72 h. The FAME conversion decreased to 71% after catalyzing three reactions with the same lipase batch.